KOMPLEKSITAS KEHIDUPAN (ANAK) PEREMPUAN PEKERJA SEKS: ANALISIS GEGURITAN ASIH PUNK ROCK KARYA WIJI THUKUL - Joko Susilo (Lakon : Jurnal Kajian Sastra dan Budaya, 2014)
During new order regime in Indonesia, it was acclaimed that there were onlythree poets whose poetries raised the issue of regime oppression. One ofthem was Wiji Thukul who then suddenly disappeared and left no traces buthis poetries. Asih Punk Rock is one of his poetries that he wrote in Javanese.It tells a story about life of a female sex worker named Asih. By applyingMichael Riffaterre method in analyzing poetry, I discover that Wiji Thukulwere trying to raise the issue of sexual violence against women/girls anddiscrimination against female sex workers, an issue that was considered lessimportant during new order regime and even until today.